Kinetic properties of Cobalt-Titanium-Boride (Co-Ti-B) catalysts for sodium borohydride hydrolysis reaction - Aydin, Meral; Hasimoglu, Aydin; Ozdemir, Oguz Kaan (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In the present work, new and efficient Cobalt Titanium Boride (Co-Ti-B) catalysts were developed for catalytic hydrolysis reaction of alkaline NaBH4 solution. Hydrogen generation rate was measured using the ternary Co-Ti-B catalyst as a function of different Ti concentration, solution temperature, NaBH4 concentration, and NaOH (a base-stabilizer) concentration. The performance of the system was analyzed from thermodynamic points of view and compared with the pristine Co-B catalyst. In addition to high catalytic efficiency, the catalyst must also comprise important features like high stability in severe conditions and should have high tolerance against deactivation. The highest hydrogen generation rate was obtained with 5% Ti/(Ti + Co) molar ratio, and for this catalyst the optimum fuel concentration was identified as 5 wt.% NaBH4 with 5 wt.% NaOH. (C) Copyright 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Cobalt titanium boride; Sodium borohydride; Ternary catalyst; Hydrogen generation; PERFORMANCE; Chemistry; Electrochemistry; Energy & Fuels